Investigation the effects of chlorine doped graphene oxide as an electrolyte additive for gel type valve regulated lead acid batteries - Mansuroglu, Abdulmecit; Gencten, Metin; Arvas, Melih B.; Sahin, Mutlu; Sahin, Yucel (ELSEVIER, 2023)
In this study, chlorine-doped graphene oxide (Cl-GOP) was used as an additive in the fumed silica-based gel electrolyte system of Valve Regulated Lead Acid (VRLA) batteries for the first time in the literature, and the performance of the gel electrolyte was increased. In this context, chlorine-doped graphene oxide produced by electrochemical methods was characterized using spectroscopic and microscopic methods, and then it was added to the fumed silica based gel electrolyte as an additive. The amount of Cl-GOP in the gel electrolyte system was optimized using electrochemical methods and 0.6 % by mass was determined as the most suitable. Then, the stirring rate and agitation time, which are the most important parameters affecting the performance of the gel electrolyte system, were optimized and the optimum values were determined as 500 rpm and 30 min, respectively. Finally, the prepared fumed silica-based electrolyte systems and aqueous electrolyte systems were subjected to charge-discharge tests and the highest discharge capacity value was determined as 42 mAh.cm(-2) in the fumed silica-based gel electrolyte system containing Cl-GOP with 20 mA.cm(-2) charge-discharge current densities. The results showed that Cl-GOP is an important additive in the fumed silica-based gel component of gel type VRLA batteries.
Keywords: Chlorine doped graphene oxide; Gelled electrolyte; Fumed silica; Additive; Lead acid batteries; VRLA; POSITIVE ELECTROLYTE; CYCLIC VOLTAMMETRY; RENEWABLE-ENERGY; ANODE MATERIALS; PERFORMANCE; GRAPHITE; SIZE; PRECIPITATION; SILOXANE; BEHAVIOR; Energy & Fuels